Patent Foramen Ovale Closure Procedure - Arwin Saleh Mangkuanom; Doni Firman (Jurnal Kardiologi Indonesia, 2021)
Patent foramen ovale is strongly associated with cryptogenic stroke. Variousclinical trials has shown the association between cryptogenic stroke andincidence of undelrying patent foramen ovale, these trials also shown thedecrease of cryptogenic stroke incidence with the treatment of patentforamen ovale Lesion. In the absence of absolute contraindications, patientswith patent foramen ovale are advised to undergo closure. Preproceduralexaminations such as trans esophageal echocardiography and pretreatmentwith anticoagulants are required to prevent peri and postprocedural adverseevents. Currently, patent foramen ovale Closure can be done through apercutaneous access with minimal risk. Treatment of patent foramen ovalecan help decrease future incidences of strokes